The Resistance Message Against Capitalism Conveyed by the Tomato Farmers of Cikareumbi Village, Lembang, Through the Cultural Event of Rempug Tarung Adu Tomat - Reza, Faisal; Sugiarta, Nugraha (Yayasan Sinergi Kawula Muda, 2025)
This research examines the message of resistance against capitalism conveyed by the tomato farmers in Cikareumbi village of Lembang sub-district through the cultural event of Rempug Tarung Adu Tomat or, as it is simply called, the “tomato battle”. Methods: This research adopts a critical discourse approach with a qualitative method. Results: The research shows that the Cikareumbi tomato farmers present their message in two steps. Firstly, they let their tomatoes go bad. Secondly, they start the tomato battle event. In practice, the message of resistance is delivered through the symbolisms found in the tomato battle. The guards represent capitalism that has made the farmers suffer, the mask worn by the guards represents the falseness of capitalism, the tomato battle represents the unity and strength of the tomato farmers against capitalism. Meanwhile, the processing of rotten tomatoes used in the battle into fertiliser and new seeds represents their class’ independence. Conclusion: Their action is propelled by two things, i.e., the unfair price set by the bourgeoise class and the lack of government’s support for the farmers. Their resistance is ultimately against capitalism that is represented by the bourgeoise class and their message also conveys their wish to be supported by the government.